1997
DOI: 10.1093/ndt/12.5.1009
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided cannulation of the femoral vein for acute haemodialysis access

Abstract: Ultrasound-guided cannulation of the femoral vein reduces the time required for the procedure, reduces the number of passes needed to puncture the vein, and minimizes complications such as arterial puncture or haematoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 0 publications
1
43
0
1
Order By: Relevance
“…Three were excluded on the grounds that the method of allocation was unclear and the trials were not described as randomised. [19][20][21] Two quasi-randomised trials, which used alternate or sequential designs, were excluded. 22,23 No additional studies were identified from the sponsor submissions.…”
Section: Number Of Studies Identified and Excludedmentioning
confidence: 99%
See 1 more Smart Citation
“…Three were excluded on the grounds that the method of allocation was unclear and the trials were not described as randomised. [19][20][21] Two quasi-randomised trials, which used alternate or sequential designs, were excluded. 22,23 No additional studies were identified from the sponsor submissions.…”
Section: Number Of Studies Identified and Excludedmentioning
confidence: 99%
“…it was not an RCT). 20 The study involved operators who were experienced in the landmark method (but not in the use of 2-D US), working in non-emergency conditions, catheterising 66 patients (28 2-D US versus 38 landmark method) scheduled for acute dialysis. Cannulation of the FV was achieved in all patients (100%) using US and in 34 patients (89.5%) using the landmark-guided technique.…”
Section: Fv (Adults)mentioning
confidence: 99%
“…In patients who needed acute hemodialysis access, the success rate was 100% under RTUS-guidance, with a higher rate of succesful first attempts as compared to the landmark approach (92.9% versus 55.3%), and a shorter mean total procedure time (45.1±18.8 versus 79.4±61.7 seconds) [23].…”
Section: Technique and Resultsmentioning
confidence: 96%
“…In patients requiring acute hemodialysis access, femoral artery puncture occurred in 7.1% of the cases when using US-guided access, and in 15.8% of the cases when using the landmark approach [23].…”
Section: Risks and Complicationsmentioning
confidence: 99%
“…However, studies examining the use of ultrasound on femoral vein access have shown ultrasound to be superior to landmark guided technique. One study showed ultrasound-guided CFV cannulation to have a first stick success rate of 93% compared to 55% in the landmark alone group [7]. In addition, total procedure time was significantly reduced, but time to access was not significantly affected.…”
Section: Introductionmentioning
confidence: 99%